Integrated models in action: Analyzing flexibility in the Canadian power system toward a zero-emission future. (15th December 2022) - Miri, Mohammad; Saffari, Mohammadali; Arjmand, Reza; McPherson, Madeleine
Abstract: Canada's power system is directly responsible for around 8.4% of the country's greenhouse gas emissions. Integrating new variable renewable energy resources is posited as one of the core pathways to decarbonizing the system. However, the inherent variability of many renewable energy resources necessitates greater spatial and temporal flexibility. Transmission expansion can deliver spatial flexibility while bulk storage can deliver temporal flexibility. Assessing flexibility adequacy requires an operational perspective employing fine temporal and spatial resolutions. In this study, a novel bidirectionally linked framework is developed to leverage insights from both operational and planning models. Wind curtailment is selected as a metric to analyze operational flexibility, which informs iterative revisions in the planning model. The results from four cases show that: (1) Transmission and storage capacities beyond the planning model's initial output are required to maintain sufficient operational flexibility in a zero-emission power system in 2050; (2) Wind capacity overestimation in initial results must be corrected; and (3) Increased total system costs can be partially offset by improvements in wind curtailment, congestion, and load shedding. It is concluded that the iterative expansion-dispatch framework proposed in this analysis yields important insights beyond stand-alone analyses, particularly in the context of a net-zero power system. Highlights: An iterative linkage is developed for power system planning and operational model. Spatial and temporal flexibility issues are assessed using curtailment as a metric. Curtailment rates are dropped from 7.5% to 3.5% by implementing this framework. Wind and storage capacities are corrected leveraging the operational insights. Costs' additions and abatements are analyzed after flexibility improvements.